Islam and the State in Indonesia - Effendy, Bahtiar (Institute of Southeast Asian Studies, 2003)
This book explains the relationship between Islam and the state and politics in contemporary Indonesia. President Soeharto's departure from office in May 1998 brought tremendous and far-reaching impacts to Indonesia's political landscape. At least 181 new political parties came into being, a sizeable portion of which use Islam as their symbol and ideological basis.